Modern Possibilities of Using Acotiamide in the Treatment of Functional Dyspepsia - A. A. Sheptulin; Yu. S. Rabotyagova (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
Aim: to evaluate the efficacy and safety of the new prokinetic drug acotiamide in the treatment of functional dyspepsia.Key findings. Acotiamide is an antagonist of inhibitory muscarinic receptors of type 1 and 2 and a reversible inhibitor of acetylcholinesterase activity. In patients with functional dyspepsia acotiamide normalizes the accommodation of the fundal part of the stomach and accelerates delayed gastric emptying. The conducted studies have confirmed the higher efficacy of acotiamide compared to placebo in reducing the severity of such symptoms of functional dyspepsia as a feeling of epigastric postprandial fullness and bloating, early satiation. The advantage of acotiamide in comparison to other prokinetics (in particular, metoclopramide and domperidone) is the high safety of use and the absence of influence on the duration of the Q-T interval.Conclusion. The high efficacy and safety of the application makes it advisable to use acotiamide in the treatment of patients with functional dyspepsia.